HAK ASUH ANAK DIBAWAH UMUR PASCA MENINGGALNYA ORANG TUA SECARA BERSAMAAN (Studi Putusan Nomor 3315/Pdt.G/2021/PA.JB) - Agnaura Chintya Salshabilla (2022)
In social life, there is no escape from family problems concerning the upbringing of a child whose life is less fortunate. Many minors who are still not independent have been separated from their parents' obligations, one of which is because their parents have died. Therefore, minors who do not have parents must be given proper care by any party deemed entitled to care according to the law in force in Indonesia. The formulation of the problem from this research is (1) What are the rules regarding parties who are entitled to custody of minors after the death of both parents simultaneously viewed from the legal aspects that apply in Indonesia? and (2) What is the result of the judge's decision on the 3315/Pdt.G/2021/ PA.JB custody case from a legal point of view? Custody of children in civil law is called guardianship and in Islamic law it is called Hadhanah. This research is a normative juridical research with the problem approach method used is the Statute Approach, the Case Approach, and the Conceptual Approach. The results of this study indicate that child care if the parents die simultaneously must be given to parties who have economic ability and are close to the child. Although Islamic law emphasizes that the woman who is more entitled to take care of underage children from the straight line of the family, but in the Gala Sky case the woman from the straight line of the family is only on the side of her father's family, namely Hj. Faisal. This study recommends the need for firmness on the rules for selecting the competent authorities in the care of minors so that children's lives in Indonesia can be more decent even though their parents are dead.